THE METHODS OF ASSESSING VISUAL ACUITY IN CHILDREN IN COMMUNITY SETTING IN MALANG - Kusuma, Ifada Hariani; Khuluqi, Rofa Husnul; Anandita, Nanda Wahyu (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesEarly visual acuity assessment in children is crucial for conducting early intervention to improvetheir literation quality. The examination in children often experiences difficulties, thus appropriateapproach and method are needed. The objective of this examination is to measure visual acuity inchildren using four different methods. MethodsThis observational-descriptive study with cross-sectional design was established based on secondarydata collected through community service setting in two orphanages in Malang. This study includedchildren with an age range from 0.5 year-old to 12 year-old. All children underwent visual acuityexamination using Lea numbers, Lea symbols, Ivory Ball, and Mounted Ball. ResultsA total of 57 children underwent visual acuity examination. The mean age of subjects was 5.9 (SD3.05) year-old. The caretaker of the orphanage had been informed and consented about theexamination and data analysis. Among those children, 26 (45.6%) were examined with Lea numbers,19 (33.3%) children with Lea symbols, 6 (10.5%) children with Ivory Ball, and 6 (10.5%) childrenwith Mounted Ball. The examination results were 33 (57.9%) children who had normal visual acuity,14 (24.6%) children with mild visual impairment, 7 (12.3%) children with moderate visualimpairment, 1 (1.8%) child with severe visual impairment, and 1 (1.8%) child considered blind. ConclusionLea numbers, Lea symbols, Ivory Ball, and Mounted Ball could be used effectively to measurechildren visual acuity in community setting.